A Novel MR Imaging Sequence of 3D-ZOOMit Real Inversion-Recovery Imaging Improves Endolymphatic Hydrops Detection in Patients with Ménière Disease - Li, J.; Sun, L.; Hu, N.; Li, L.; Song, G.; Xu, H.; Xu, T.; Cheng, Y.; Xiao, L.; Wang, L.; Gong, R.; Li, C. (American Journal of Neuroradiology, 2023)
BACKGROUND AND PURPOSE: The detection rate of premortem MR imaging endolymphatic hydrops is lower than that of postmortem endolymphatic hydrops in Ménière disease, indicating that current MR imaging techniques may underestimate endolymphatic hydrops. Therefore, we prospectively investigated whether a novel high-resolution MR imaging technique, the 3D zoomed imaging technique with parallel transmission real inversion-recovery (3D-ZOOMit real IR), would improve the detection of endolymphatic hydrops compared with conventional 3D TSE inversion-recovery with real reconstruction.MATERIALS AND METHODS: Fifty patients with definite unilateral Ménière disease were enrolled and underwent 3D-ZOOMit real IR and 3D TSE inversion-recovery with real reconstruction 6 hours after IV gadolinium injection. The endo- and perilymph spaces were scored separately. The contrast-to-noise ratio, SNR, and signal intensity ratio of the 2 sequences were respectively calculated and compared. The presence of endolymphatic hydrops was evaluated.RESULTS: The endolymphatic space in the cochlea and vestibule was better visualized with 3D-ZOOMit real IR than with conventional 3D TSE inversion-recovery with real reconstruction (P < .001). There were differences between the 2 sequences in the evaluation of no cochlear hydrops and cochlear hydrops (both, P < .017). All contrast-to-noise ratio, SNR, and signal intensity ratio values of 3D-ZOOMit real IR images were statistically higher than those of conventional 3D TSE inversion-recovery with real reconstruction (all, P < .001).CONCLUSIONS: The 3D-ZOOMit real IR sequences are superior to conventional 3D TSE inversion-recovery with real reconstruction sequences in visualizing the endolymphatic space, detecting endolymphatic hydrops, and discovering contrast permeability.CNRcontrast-to-noise ratio3D real IR3D inversion-recovery with real reconstructionEHendolymphatic hydropsFOVfield of viewMDMénière diseaseSIsignal intensitySPACEsampling perfection with application-optimized contrasts by using different flip angle evolutionSIRsignal-intensity ratiot-3D real IR3D TSE inversion-recovery with real reconstructionZOOMitzoomed imaging technique with parallel transmissionzs-3D real IR3D ZOOMit SPACE real inversion-recovery